Digital Transformation in HRM: Leveraging AI and Big Data for Employee Engagement and Retention - Qawasmeh, Esraa; Qawasmeh, Farid; Daoud, Mohammad Khalaf (Journal of Ecohumanism, 2024)
The Jordanian banking sector is now seeing a significant change in the use of artificial intelligence (AI) and big data in human resource management (HRM). To assess the influence of this era on employee engagement and retention, 300 employees of Jordanian bank were the sample of the study. Using partial least squares (PLS) structural equation modeling, we have a look at investigating how pride mediates and organizational culture modifies those effects. The study found a favorable correlation between AI adoption (r = 0.65, p < 0.01) and Big Data use (r = 0.58, p < 0.05) and work satisfaction, organizational culture, savings technology, staff engagement, and positive connections with Jordanian savings banks. Furthermore, regression research demonstrates that AI adoption and usage of Big Data are predictive. AI and big data can optimize HRM practices and provide insights, leading to higher employee satisfaction (r = 0.72, p < 0.01). This can enhance competitive advantage and strategy in the digital age.